2021
DOI: 10.1017/s1047951120004746
|View full text |Cite
|
Sign up to set email alerts
|

Midodrine treatment in children with recurrent vasovagal syncope

Abstract: Background: Vasovagal syncope is the most common cause of syncope in childhood and its treatment is not at a satisfactory level yet. We aimed to investigate patients who were diagnosed with vasovagal syncope, did not benefit from conventional treatment, received midodrine treatment, and to evaluate their response to midodrine treatment. Methods: Files of 24 patients who were diagnosed with recurrent vasovagal syncope, did not benefit from non-pharmacological treatments, and received mido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Additionally, the use of progressively prolonged periods of enforced upright posture, known as “tilt training,” may reduce syncope recurrence in highly motivated patients with recurrent vasovagal symptoms [ 32 ]. Other therapies for VVS include increased salt and water intake and various drug treatments (such as atenolol [ 33 ] and midodrine [ 34 ]). Furthermore, the effectiveness of β-blockers in preventing VVS has been found to be age-dependent, with potential effectiveness in older patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the use of progressively prolonged periods of enforced upright posture, known as “tilt training,” may reduce syncope recurrence in highly motivated patients with recurrent vasovagal symptoms [ 32 ]. Other therapies for VVS include increased salt and water intake and various drug treatments (such as atenolol [ 33 ] and midodrine [ 34 ]). Furthermore, the effectiveness of β-blockers in preventing VVS has been found to be age-dependent, with potential effectiveness in older patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Midodrine offers a major advantage over other vasoconstrictors due to its oral administration, avoiding the need for hospitalization, lower cost, and relative safety compared to other splanchnic vasoconstrictors 2–5 . Previous use of midodrine in children with vasovagal syncope and postural tachycardia syndrome has demonstrated safety, although the optimal pediatric dosage remains unclear 18,19 …”
Section: Discussionmentioning
confidence: 99%
“…Midodrine is an approved agent for orthostatic hypotension management in the United States ( Low et al, 1997 ), the beneficial effects of midodrine have been confirmed in a series of studies on adult VVS ( Samniah et al, 2001 ; Kaufmann et al, 2002 ). However, the efficacy of midodrine hydro-chloride in children and adolescents is variable ( Mitro et al, 1999 ; Kaufmann et al, 2002 ; Qingyou et al, 2006 ; Romme et al, 2011 ; Bagrul et al, 2021 ). Great improvements were achieved in terms of individualized therapies and before the application of any treatment, biological markers or predictors could provide useful information for doctors to choose a specific treatment regimen.…”
Section: Discussionmentioning
confidence: 99%